CO2 flooding effects and breakthrough times in low-permeability reservoirs with injection–production well patterns containing hydraulic fractures - Nanlin Zhang; Bin Cao; Fushen Liu; Liangliang Jiang; Zhifeng Luo; Pingli Liu; Yusong Chen (Natural Gas Industry B)
Comprehensive studies on CO2 breakthrough times and flooding effects are crucial for optimizing CO2 flooding strategies. This study utilized numerical simulations to investigate the effects of hydraulic fractures, permeability, and CO2 injection rates on CO2 breakthrough times and cumulative oil production. Nonlinear relationships among the respective variables were established, with Sobol method analysis delineating the dominant control factors. The key findings indicate that although hydraulic fracturing shortens CO2 breakthrough time, it concurrently enhances cumulative oil production. The orientation of hydraulic fractures emerged as a pivotal factor influencing flooding effectiveness. Furthermore, lower permeability corresponds to lower initial oil production, while higher permeability corresponds to higher initial daily oil production. When reservoir permeability is 1 mD, oil production declines at 1000 days, and at 2 mD, it declines at 700 days. At a surface CO2 injection rate of 10,000 m3/d, the daily oil production of a single well is approximately 7.5 m3, and this value remains relatively stable over time. The hierarchical order of influence on CO2 breakthrough and rapid rise times, from highest to lowest, is permeability, well spacing, CO2 injection rate, porosity, and hydraulic fracture conductivity. Similarly, the order of influence on cumulative oil production, from highest to lowest, is well spacing, porosity, permeability, CO2 injection rate, and hydraulic fracture conductivity. This paper analyzed the impact of geological and engineering parameters on CO2 flooding and oil production and provided insights to optimize CO2 injection strategies for enhanced oil recovery.